Penerapan Transaksi Non Tunai dalam Praktek Notaris Terhadap Akad Mudharabah di Perbankan Syariah - Satrio Abdillah (Lex Renaissance, 2017)
AbstractNon-cash transactions in Mudharabah contract is one of several types of contract in Islamic banking. Mudaraba is a contract based on revenue sharing, in which Islamic banks bear the full needs of venture capital / investment. This study focused on the problem of how the application of non-cash transactions in mudharabah in Islamic banking and whether the scheme of non-cash transactions in Islamic banking mudharabah in accordance with Shari'a principles truth. This study is a juridical-empirical research using primary data, secondary and tertiary. The results showed the first application of non-cash transactions in Islamic banking in Indonesia, many of which deviated from the terms of the principle, tend to be mere labeling (labeling). Due Both mudaraba product does not comply with the principle of mudaraba beginning itself so judged only in the form of labeling (labeling) only from the bank and the necessity to not give a guarantee that is incompatible with God's word QS. Al-Baqarah (2) paragraph 282-283.Keywords: Islamic banking, mudaraba, deed, security (collateral)